Health Promotion Using Counseling Cards to Increase Perceived Benefit, Perceived Barrier, and Self-Efficacy for Congenital Hypothyroid Screening - Dede Gantini; Sariestya Rismawati; Dita Eka Mardiani; Rahmi Nursyadiah (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Congenital hypothyroid screening coverage in Indonesia remains low (2.3%), partly due to limited effective health promotion and inadequate use of educational media, leading to low maternal participation. Strengthening health promotion through appropriate media and optimizing the role of health cadres are essential to improving mothers’ perceived benefits, reducing perceived barriers, and enhancing self-efficacy for screening. This study aimed to analyze the effect of education delivered through counseling cards by health cadres on mothers' perceived benefits, perceived barriers, and self-efficacy in conducting congenital hypothyroid screening. A quasi-experimental pre–post test design was conducted in Tasikmalaya City, involving 41 third-trimester pregnant women selected via quota sampling from 20 primary health center service areas. Trained cadres provided education using counseling cards. Data were collected before and after the intervention using validated questionnaires measuring perceived benefit, perceived barrier, and self-efficacy. Data analysis showed significant improvements in all variables after the intervention (p < 0.05). In conclusion, counseling card–based education is effective in improving mothers’ perceived benefits, perceived barriers, and self-efficacy toward congenital hypothyroid screening. It is recommended that this approach be integrated into routine maternal health promotion and scaled up through community health cadres to enhance screening uptake and support early detection at the population level.